Rationalizing Korea : the rise of the modern state, 1894-1945 - Hwang, Kyung Moon (Oakland, California : University of California Press, 2016)
"The first book to explore the institutional, ideological, and conceptual development of the modern state on the peninsula, Rationalizing Korea analyzes the state's relationship to five social sectors, each through a distinctive interpretive theme: economy (developmentalism), religion (secularization), education (public schooling), population (registration), and public health (disease control). Kyung Moon Hwang argues that while this formative process resulted in a more commanding and systematic state, it was also highly fragmented, socially embedded, and driven by competing, often conflicting rationalizations, including those of Confucian statecraft and legitimation. Such outcomes reflected the acute experience of imperialism, nationalism, colonialism, and other sweeping forces of the era"--Provided by publisher.
State making under imperialism: fragmentation and consolidation in the central state -- The centrality of the periphery: developing the provincial and local state -- Constructing legitimacy: symbolic authority and ideological engineering -- State and economy: developmentalism -- State and religion: secularization and pluralism -- Public schooling: cultivating citizenship education -- Population management: registration, classification, and the remaking of society -- Public health and biopolitics: disciplining through disease control.
Incluye referencias bibliográficas (páginas 349-378) e índice.
Keywords: Administración Pública -- Korea; Korea -- Política y gobierno -- 1864-1910.; Korea -- Política y gobierno -- 1910-1945.; Korea -- Social policy -- 19th century; Korea -- Social policy -- 20th century